The Main Factors Causing the Incidence of Diarrhea in Children: A Meta-Analysis - Eny Rohmawaty; R. Azizah (Poltekita : Jurnal Ilmu Kesehatan, 2023)
Environmental factors that cause diarrhea are still under-researched, so researchers are interested analyze the risk factors for the availability of clean water, hand washing, mother's knowledge and the latrine conditions that affect the incidence of diarrhea in toddlers. The meta-analysis method was used in this study with the PICOS technique. Some of the data sources used are Google Scholar, Research Gate and Plos ONE by looking at keywords such as "risk factors" and "diarrhea". 140 articles were obtained, and the articles obtained were then screened and sorted again using clear inclusion criteria. Using cross-sectional study design to filter the articles to the next stage. To process the meta-analysis data, the JASP Version 0.16.3.0 application was used. the findings show that the pooled PR value for the availability of clean water is e 0.82 = 2.270; hand washing of e 0.57 = 1.768; mother's knowledge of e 0.56 = 1.751; and latrine conditions of e 0.53 = 1.699. The results of the study also showed that there was a risk relationship between the variables Availability of clean water, hand washing, mother's knowledge, and latrine conditions on the incidence of diarrhea in toddlers. The variable availability of clean water is the variable that has the highest relationship and risk for the incidence of diarrhea in toddlers, followed by the hand washing, the mother's knowledge and the lowest is the latrine condition variable. Future research is expected to examine the in-depth relationship between the availability of clean water and hand washing by looking at the intermediary factors.